THE INFLUENCE OF PARENTAL SUPPORT AND LEARNING ENVIRONMENT ON STUDENT LEARNING ENTHUSIASM THROUGH LEARNING MOTIVATION AS AN INTERVENING VARIABLE (STUDY ON FEB UNJ STUDENTS) - Yanti, Lina Dewi; Stefany, Teresa; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to examine the direct and indirect effects of parental support and the learning environment on student’s learning enthusiasm, with learning motivation as a mediating variable. The research was conducted among students of the Faculty of Economics and Business, Universitas Negeri Jakarta (UNJ), using a quantitative approach with survey methods. A total of 100 respondents were selected through purposive sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings suggest that parental support and the learning environment do not significantly impact learning motivation, nor do they directly influence student’s learning enthusiasm. However, learning motivation has a strong and significant direct effect on learning enthusiasm. Furthermore, the indirect effect of parental support and the learning environment on learning enthusiasm through learning motivation is also not significant. These results highlight the dominant role of internal student motivation in fostering enthusiasm for learning, while external factors such as parental support and learning environment serve as supporting elements rather than primary drivers. Beyond academic insights, this study contributes to the broader understanding of human capital development, especially in the context of modern HRM, where motivation and support systems are essential in shaping productive and engaged individuals.